The impact of the COVID-19 pandemic on the quality of higher medical education - Vidin Kirkov (Pensoft Publishers, 2024)
The COVID-19 pandemic was an unprecedented test for the whole sociological structure of society, which includes all the basic spheres and main areas of public life. The biggest test was for health systems, as they had to contend with, on the one hand, a hitherto unknown disease and, on the other, reorganize its overall treatment and diagnostic activity in accordance with the anti-epidemic measures introduced by the state authorities. This is inevitable and has influenced and left its mark on the medical training of future health personnel, which is carried out for the most part in the university medical facilities that were on the front lines in the fight against the pandemic. This article presents an analysis of data from empirical research on the impact of the COVID-19 pandemic on the quality of higher medical education.